HUBUNGAN PERSEPSI SUAMI TENTANG KB VASEKTOMI DENGAN MINAT MEMAKAI KB VASEKTOMI DI DESA BANDUNG KECAMATAN GEDEG KABUPATEN MOJOKERTO - Saudah, Noer; Laila Rachmawati, Nur (JURNAL KEPERAWATAN SEHAT, 2016)
The family planning program to this day has not been able to mentransfusi understanding of the views of men who still think that family planning is the business of women. the low participation of men in family planning, among others due to lack of knowledge and information, lack of awareness and lack of socialization is clearly and correctly about KB Men Long term vasectomy or MOP. The purpose of this study was to determine the correlation of husbands perception about the KB Vasectomy Vasectomy interest in using birth control. This study used cross sectional analytical design. The population in this study are all husbands who still has a wife of reproductive age in the Ngudilor hamlet Bandung village Gedeg District of Mojokerto regency as many as 164 people. Sample of 62 respondents drawn using simple random sampling technique. Sources of data used primary data, the instrument uses a questionnaire distributed to respondents. The data analysis using Chi Square. The result showed most husbands have negative perceptions about KB MOP as many as 40 respondents (64.5%) and most husbands have negative interests or not interested in participating KB MOP as many as 43 respondents (69.4%). Chi Square test results obtained probability value 0.000 <0.05, which means there is a correlation husbands perception about KB Vasectomy interests using contraception Vasectomy in Hamlet Village NgudilorGedeg Bandung District of Mojokerto. The husband must frequently access information about KB MOP about the good and bad for the health or life of the household and the wife always talked about the use of birth control.Keywords: perception, husband, KB Vasectomy, interests